2021
DOI: 10.3390/antiox10010104
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Thioredoxin and Glutathione Systems’ Response in Lymphoma Cells after Treatment with [Au(d2pype)2]Cl

Abstract: Lymphoma is a blood cancer comprising various subtypes. Although effective therapies are available, some patients fail to respond to treatment and can suffer from side effects. Antioxidant systems, especially the thioredoxin (Trx) and glutathione (GSH) systems, are known to enhance cancer cell survival, with thioredoxin reductase (TrxR) recently reported as a potential anticancer target. Since the GSH system can compensate for some Trx system functions, we investigated its response in three lymphoma cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Their effects on BCR-ABL and CML cell death have been thoroughly documented; however, the degree of drug resistance that is associated with them is also well known [40][41][42]. It has previously been shown that the inhibition of the TRX system downregulates the activity of BCR-ABL and thus induces apoptosis in CML cells; however, the inhibition of the TRX system in itself also results in apoptosis [43,44]. Therefore, we wanted to investigate whether this interaction functions both ways and if the inhibition of BCR-ABL would lead to a decrease in the activity of the TRX system and thus cause apoptosis via this mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their effects on BCR-ABL and CML cell death have been thoroughly documented; however, the degree of drug resistance that is associated with them is also well known [40][41][42]. It has previously been shown that the inhibition of the TRX system downregulates the activity of BCR-ABL and thus induces apoptosis in CML cells; however, the inhibition of the TRX system in itself also results in apoptosis [43,44]. Therefore, we wanted to investigate whether this interaction functions both ways and if the inhibition of BCR-ABL would lead to a decrease in the activity of the TRX system and thus cause apoptosis via this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of BCR-ABL by TKIs resulted in a decrease in the expression and activity of the TRX system, likely through the action of PKC. BCR-ABL was shown to activate PKC[44,45], which is a known regulator of NRF2[12]. The lower activity levels of the TRX system resulted in an increase in ROS, which can lead to apoptosis through a range of mechanisms, including direct damage to DNA, lipids and proteins and the activation of cell death pathways, such as the ASK1 pathway.…”
mentioning
confidence: 99%
“…Brown block-like single crystals suitable for X-ray diffraction analysis were obtained after about two weeks through partial evaporation of the solvent. Yield: 35 Characterization and structural analysis of the CuCP. The crystals of CuCP were separated from the mother liquor for X-ray crystallography analysis.…”
Section: Synthesis and Structural Analysismentioning
confidence: 99%
“…Several materials, including iron, copper, and manganese ions, have been demonstrated so far to perform CDT on cancer by generating ROS in cells. [29][30][31] However, the presence of overexpressed antioxidants such as glutathione (GSH), 32 superoxide dismutase (SOD) 33 and thioredoxin (Trx) 34 /thioredoxin reductase (TrxR) in tumor cells 35 still restricts CDT. 36,37 In particular, high concentrations of GSH in cancer cells have a strong scavenging effect on corticotropin, 38 thereby greatly enhancing the resistance of cancer cells to oxidative stress and reducing the efficacy of CDT.…”
Section: Introductionmentioning
confidence: 99%
“…GSH and thioredoxin (Trx) are believed to be two antioxidant pathways generally work together to facilitate tumor progression [ 5 , 6 ]. Therefore, dual inhibition of these two systems might promise synergistic effects in killing cancer cells.…”
Section: Introductionmentioning
confidence: 99%